Air-stable, earth-abundant molten chlorides and corrosion-resistant containment for chemically-robust, high-temperature thermal energy storage for concentrated solar power. (June 2021) - Caldwell, Adam S.; Itskos, Grigorios; Sandhage, Kenneth H.
Graphical abstract: Abstract: A dramatic reduction in man-made CO2 emissions could be achieved if the cost of electricity generated from concentrated solar power (CSP) plants could become competitive with fossil-fuel-derived electricity. The solar heat-to-electricity conversion efficiency of CSP plants may be significantly increased (and the associated electricity cost decreased) by operating CSP turbines with inlet temperatures ≥750 °C instead of ≤550 °C, and by using thermal energy storage (TES) at ≥750 °C to allow for rapidly dispatchable and/or continuous electricity production. Unfortunately, earth-abundant MgCl2 –KCl-based liquids currently being considered as low-cost media for large-scale, high-temperature TES are susceptible to oxidation in ambient air, with associated undesired changes in liquid composition and enhanced corrosion of metal alloys in pipes and tanks containing such liquids. In this paper, alternative high-temperature, earth-abundant molten chlorides that are resistant to oxidation in ambient air are identified via thermodynamic calculations. The oxidation resistance, and corrosion-resistant containment, of such molten chlorides at 750 °C are then demonstrated. Such an air-tolerant strategy, involving chemically-robust, low-cost TES media paired with effective containment materials, provides a critical advance towards the higher-temperature operation of, and lower-cost electricity generation from, CSP plants.